Outcomes of Treated Hypertension at Age 80 and Older: Cohort Analysis of 79, 376 Individuals. Issue 5 (30th December 2016) - Delgado, João; Masoli, Jane A. H.; Bowman, Kirsty; Strain, W. David; Kuchel, George A.; Walters, Kate; Lafortune, Louise; Brayne, Carol; Melzer, David; Ble, Alessandro; ,
Abstract : Objectives: To estimate outcomes according to attained blood pressure (BP) in the oldest adults treated for hypertension in routine family practice. Design: Cohort analysis of primary care inpatient and death certificate data for individuals with hypertension. Setting: Primary care practices in England (Clinical Practice Research Datalink). Participants: Individuals aged 80 and older taking antihypertensive medication and free of dementia, cancer, coronary heart disease, stroke, heart failure, and end‐stage renal failure at baseline. Measurements: Outcomes were mortality, cardiovascular events, and fragility fractures. Systolic BP (SBP) was grouped in 10‐mmHg increments from less than 125 to 185 mmHg or more (reference 145–154 mmHg). Results: Myocardial infarction hazards increased linearly with increasing SBP, and stroke hazards increased for SBP of 145 mmHg or greater, although lowest mortality was in individuals with SBP of 135 to 154 mmHg. Mortality of the 13.1% of patients with SBP less than 135 mmHg was higher than that of the reference group (Cox hazard ratio=1.25, 95% confidence interval=1.19–1.31; equating to one extra death per 12.6 participants). This difference in mortality was consistent over short‐ and long‐term follow‐up; adjusting for diastolic BP did not change the risk. Incident heart failure rates were higher in those with SBP less than 125 mmHg than in the reference group. Conclusion: In routine primary care, SBP less than 135 mmHg was associated with greater mortality in the oldest adults with hypertension and free of selected potentially confounding comorbidities. Although important confounders were accounted for, observational studies cannot exclude residual confounding. More work is needed to establish whether unplanned SBPs less than 135 mmHg in older adults with hypertension may be a useful clinical sign of poor prognosis, perhaps requiring clinical review of overall care.